Możliwości konkurencyjne przedsiębiorstw wobec procesu koncentracji handlu detalicznego w warunkach rynku unijnego - Grzybek, Maria; Cyrek, Piotr (Competitive Possibilities of Enterprises in the Face of Process of Retail Trade Concentration in the Conditions of the Union Market, 2005)
Integration processes essentially influence conditions of conducting activity in the sphere of retail trade. Observed expansion of foreign chains can constitute a threat for functioning of small Polish enterprises but at the same time releases innovative and cooperative behaviours increasing competitiveness of domestic units. In the study there are presented opinions of country and city entrepreneurs from the Podkarpackie voivodeship - acting in retail trade, concerning the most important megatrends and possibilities ensuing from the integration processes. They perceive existing threats but using previously gained strengths and opportunities derived from the European integration are able to compete on the new open market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 321-326